Carbon-silicon composite negative electrode material and preparation method thereof

CN122950451APending Publication Date: 2026-10-20CHINA SALT CHANGZHOU CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611239617.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

以解决现有技术中硅碳界面结合力不足、单一碳包覆层难以兼顾机械约束与离子传输效率、循环稳定性差的技术问题

Benefits of technology

(1)本发明通过原位反应在硅核表面形成SiC过渡层,实现硅碳界面的原子级Si-C化学键合,显著增强了硅核与碳层之间的结合力,有效防止硅颗粒在循环过程中从碳骨架上脱落;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to a carbon-silicon composite anode material and its preparation method, belonging to the technical field of lithium-ion battery anode materials. It comprises a 50-200 nm silicon nanoparticle core, a 5-20 nm thick SiC transition layer, and a 20-50 nm thick highly conductive amorphous carbon outer layer. The SiC transition layer is formed in situ by introducing an organosilicon precursor and a carbon source gas into the silicon nanoparticles at 600-800°C; subsequently, an amorphous carbon layer is deposited at 400-600°C; and finally, heat treatment annealing is performed. This application achieves strong coupling at the silicon-carbon interface through atomic-level Si-C chemical bonding. The SiC layer provides mechanical anchoring and stress buffering, while the carbon layer provides efficient electronic conduction, synergistically solving the problem of insufficient silicon-carbon interface bonding, significantly improving cycle stability and fast-charging performance. The process is highly controllable and easily scaled up for industrial applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a carbon-silicon composite anode material and its preparation method, belonging to the technical field of lithium-ion battery anode materials. Background Technology

[0002] Currently, lithium-ion batteries, as the most promising energy storage devices, rely on innovation in anode materials to improve their energy density. Silicon-based anode materials have a theoretical capacity of up to 4200 mAh / g, more than ten times that of traditional graphite anodes, and are considered ideal anode materials for next-generation high-energy-density lithium-ion batteries.

[0003] However, silicon anode materials suffer from severe volume expansion during charge and discharge. During lithium-ion insertion, the volume of silicon can expand by 300%-400%, leading to a series of technical problems: silicon particles crack or even pulverize during repeated expansion and contraction, causing electrical contact breakdown between the active material and the current collector; the silicon surface is continuously exposed to the electrolyte, forming an unstable solid-state electrolyte interface (SEI) film, which repeatedly ruptures and regenerates, consuming the active lithium source; in traditional silicon-carbon composites, the bond between silicon nanoparticles and the carbon skeleton is mostly a simple physical mixture or weak chemical bond, resulting in insufficient adhesion. During cycling, silicon easily detaches from the carbon skeleton, causing the internal conductive network to break.

[0004] To address the aforementioned issues, various carbon-coated silicon composite structures have emerged in existing technologies. For example, a carbon layer is deposited on the surface of silicon particles using chemical vapor deposition or pyrolysis to form a core-shell structure. However, traditional single carbon coating layers have the following drawbacks: the thermal expansion coefficients between the carbon shell and the silicon core differ significantly, leading to cracking and detachment of the carbon coating layer during long-term cycling due to stress concentration; a single carbon coating layer struggles to simultaneously achieve good mechanical confinement and efficient lithium-ion transport channels, resulting in high interfacial impedance and limited high-rate charge / discharge performance.

[0005] Therefore, how to achieve strong atomic-level coupling at the silicon-carbon interface and construct a carbon-silicon composite anode material structure that combines mechanical stability with efficient ion-electron transport capability remains a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] To address the aforementioned technical problems, the present invention aims to provide a carbon-silicon composite anode material and its preparation method. This addresses the technical issues in the prior art, such as insufficient silicon-carbon interfacial bonding, the difficulty of a single carbon coating layer in balancing mechanical constraint and ion transport efficiency, and poor cycle stability.

[0007] The present invention provides a carbon-silicon composite anode material comprising:

[0008] Nano-silicon cores, which are silicon particles with a particle size of 50-200 nm, serve as active materials to provide lithium-ion storage capacity. The nano-SiC transition layer is a silicon carbide layer formed in situ by reaction with a thickness of 5-20 nm. It is located on the surface of the nano-silicon core and is tightly bonded to the silicon core through atomic-level Si-C chemical bonding. A highly conductive amorphous carbon outer layer, wherein the highly conductive amorphous carbon outer layer is an amorphous carbon layer with a thickness of 20-50 nm, which is coated on the outside of the SiC transition layer to form a three-dimensional conductive network.

[0009] Based on the total mass of the SiC transition layer, the content of the SiC phase in the transition layer can be precisely controlled by adjusting the flow rate ratio of silane to carbon source gas.

[0010] The preparation method of the carbon-silicon composite anode material includes the following steps: (1) Pretreatment: The silicon source material is nano-sized to obtain nano-silicon particles with a particle size of 50-200nm, which are dispersed in an inert atmosphere for later use. (2) In-situ generation of SiC transition layer: The nano-silicon particles are placed in a chemical vapor deposition apparatus and heated to 600-800℃; Simultaneously, organosilicon precursor and carbon source gas are introduced; In a high-temperature gas phase environment, silicon generated from the pyrolysis of organosilicon precursor and carbon generated from the cracking of carbon source gas react in situ on the surface of silicon particles to form a nanoscale SiC transition layer with a thickness controlled at 5-20 nm. (3) Deposition of amorphous carbon layers: The reaction temperature was lowered to 650~750℃; carbon source gas was continued to be introduced for gas phase pyrolysis deposition, forming a continuous highly conductive sp² / sp³ mixed amorphous carbon layer on the outside of the SiC transition layer, with the thickness controlled at 20-50nm.

[0011] (4) Post-processing: Cool to room temperature, collect the double-coated carbon-silicon composite particles, and perform heat treatment annealing to optimize the crystal structure.

[0012] Furthermore, the organosilicon precursor is a silane; Furthermore, the carbon source gas is C2H2, CH4, or a mixture thereof; Furthermore, in steps (2) and (3), magnetron sputtering or plasma-enhanced chemical vapor deposition techniques can be used to achieve uniform deposition and precise thickness control of the coating layer.

[0013] Furthermore, by adjusting the flow ratio of the organosilicon precursor to the carbon source gas, the SiC phase content can be precisely controlled, with the SiC mass fraction content preferably ranging from 5% to 30%.

[0014] By means of the above-described solution, the present invention has at least the following advantages: (1) The present invention forms a SiC transition layer on the surface of silicon core through in-situ reaction, realizing atomic-level Si-C chemical bonding at the silicon-carbon interface, which significantly enhances the bonding force between silicon core and carbon layer and effectively prevents silicon particles from falling off the carbon skeleton during cycling. (2) The SiC transition layer of the present invention provides mechanical anchoring and charge / discharge volume stress buffering effect, solving the problem of easy peeling of silicon-carbon interface; the outer sp² / sp³ hybrid amorphous carbon constructs a continuous three-dimensional conductive network, making up for the defects of poor intrinsic conductivity and high ion diffusion resistance of SiC. The two work together to achieve structural stability and excellent electron lithium-ion transport capability.

[0015] (3) The composite anode material prepared by the present invention is expected to achieve excellent performance of first-time efficiency >92%, interface impedance <50Ω·cm², and 3C fast charging capacity retention rate >80%. By adjusting the deposition temperature, gas phase composition and reaction time, the thickness of SiC transition layer and amorphous carbon layer and SiC phase content can be precisely controlled. The process window is wide and easy to scale up industrially.

[0016] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below. Detailed Implementation

[0017] The specific embodiments of the present invention will be described in further detail below with reference to the examples. These examples are for illustrative purposes only and are not intended to limit the scope of the invention.

[0018] A carbon-silicon composite anode material and its preparation method, comprising: Nano-silicon cores, which are silicon particles with a particle size of 50-200 nm, serve as active materials to provide lithium-ion storage capacity. The nano-SiC transition layer is a silicon carbide layer formed by in-situ reaction with a thickness of 5-20 nm. It is located on the surface of the nano-silicon core and is tightly bonded to the silicon core through atomic-level Si-C chemical bonding. A highly conductive amorphous carbon outer layer, the amorphous carbon layer having a thickness of 20-50 nm, is coated on the outside of the SiC transition layer to form a three-dimensional conductive network.

[0019] The SiC phase content in the SiC transition layer can be controlled by adjusting the ratio of organosilicon precursor to carbon source gas.

[0020] The preparation method of the carbon-silicon composite anode material includes the following steps: (1) Pretreatment: The silicon source material is nano-sized to obtain nano-silicon particles with a particle size of 50-200nm, which are dispersed in an inert atmosphere for later use. (2) In-situ formation of SiC transition layer: Nano-silicon particles are placed in a chemical vapor deposition apparatus and heated to 600-800℃; at the same time, an organosilicon precursor and a carbon source gas are introduced; in the high-temperature gas phase environment, silicon generated by the pyrolysis of the organosilicon precursor and carbon generated by the cracking of the carbon source gas react in-situ on the surface of the silicon particles to form a nano-scale SiC transition layer with a thickness controlled at 5-20nm; the organosilicon precursor is silane; the carbon source gas is C2H2, CH4 or a mixture thereof; (3) Amorphous carbon layer deposition: reduce the reaction temperature to 650~750℃; continue to introduce carbon source gas for gas phase pyrolysis deposition, and form a continuous high conductivity sp² / sp³ mixed amorphous carbon layer on the outside of the SiC transition layer, with the thickness controlled at 20-50nm.

[0021] (4) Post-processing: Cool to room temperature, collect the double-coated carbon-silicon composite particles, and perform heat treatment annealing to optimize the crystal structure.

[0022] In steps (2) and (3), magnetron sputtering or plasma-enhanced chemical vapor deposition (PECVD) techniques can be used to achieve uniform deposition and precise thickness control of the coating layer.

[0023] By adjusting the flow ratio of the organosilicon precursor to the carbon source gas, the SiC phase content can be precisely controlled, with the SiC content ranging from 5% to 30%.

[0024] Example Example 1 Preparation of a silicon-carbon interface atomically coupled dual-coating structure carbon-silicon composite anode material In this embodiment, a SiC transition layer is formed in situ on the surface of nano-silicon particles using chemical vapor deposition (CVD) technology, and an amorphous carbon outer layer is deposited by vapor phase pyrolysis to prepare a double-coated carbon-silicon composite anode material with an atomic-level coupling interface.

[0025] (1) Preparation of nano-silicon particles Commercially available micron-sized silicon powder (purity ≥99.9%) was nano-sized using high-energy ball milling. The milling conditions were: milling speed 1200 rpm, ball-to-powder ratio 20:1, milling time 8 h, and ethanol as the grinding medium. After milling, the powder was vacuum-dried at 80℃ for 6 h to obtain silicon nanoparticles with a particle size of 80-150 nm. The morphology and particle size distribution were characterized using scanning electron microscopy (SEM) and laser particle size analyzer, confirming that the particle size met the design requirements.

[0026] (2) In-situ formation of SiC transition layer Nano-silicon particles are uniformly spread on a graphite tray of a chemical vapor deposition (CVD) apparatus and loaded into the deposition chamber. After evacuating to a base pressure of less than 10 Pa, high-purity argon gas (purity ≥ 99.999%) is introduced to replace the atmosphere, and this process is repeated three times to ensure the chamber is clean.

[0027] High-purity nitrogen (purity ≥99.999%) was used as the carrier gas. Silane vapor and acetylene C2H2 gas were introduced separately. Silane was introduced through a vaporization bottle heated to 80°C. The acetylene gas flow rate was controlled at 20-50 sccm. The silane vapor flow rate was adjusted by the carrier gas flow rate and controlled at 10-30 sccm.

[0028] The resistance heating device is activated to raise the temperature of the deposition zone to 700℃, and maintained at this temperature for 30-60 minutes. In this high-temperature gas phase environment, the Si vapor generated by silane pyrolysis reacts in situ with the C generated by acetylene decomposition on the surface of the nano-silicon particles, forming a nanoscale SiC transition layer. By controlling the reaction time and gas phase composition, the thickness of the SiC transition layer is controlled to 10-15 nm. The specific reaction equation can be expressed as follows: SiH4→Si+2H2 C2H2→2C+H2 Si + C → SiC (3) Deposition of amorphous carbon layers The heating temperature is reduced to 700℃, and acetylene gas is continuously introduced at a flow rate of 50-80 sccm. Simultaneously, methane (CH4) is introduced as an auxiliary carbon source at a flow rate of 30-50 sccm. Within a temperature range of 650-750℃, the carbon source gas undergoes pyrolysis and deposition on the surface of the SiC transition layer, forming an amorphous carbon outer layer. The pyrolysis reaction equation is as follows: C2H2→2C+H2 CH4→C+2H2 The deposition time is controlled at 15-30 min to achieve an amorphous carbon layer thickness of 30-40 nm.

[0029] (4) Post-processing and characterization After deposition, the sample was allowed to cool naturally to room temperature and then removed. The resulting double-coated silicon-carbon composite particles were then annealed in an argon atmosphere at 600°C for 2 hours to optimize the SiC interface crystal structure and eliminate internal stress.

[0030] The microstructure of the composite material was characterized by transmission electron microscopy (TEM) to confirm the presence and thickness of the SiC transition layer and the amorphous carbon layer. The formation of the SiC phase was confirmed by X-ray diffraction (XRD) analysis of the product phase composition. Obvious SiC diffraction peaks should appear at 2θ=35.6°, 60.0°, and 71.8° in the XRD pattern. The chemical state of the interface elements was confirmed by X-ray photoelectron spectroscopy (XPS) analysis. The presence of Si-C chemical bonding was confirmed. In the XPS pattern, the Si2p orbital corresponds to the Si-Si bond at 99.5 eV and the Si-C bond at 101.5 eV.

[0031] Example 2 This embodiment employs plasma-enhanced chemical vapor deposition (PECVD) technology to prepare a double-coated carbon-silicon composite anode material, achieving more uniform coating deposition and more precise thickness control. PECVD technology utilizes plasma glow discharge to decompose the precursor gas, enabling high-quality thin film deposition at relatively low temperatures.

[0032] Nano-sized silicon particles with a diameter of 100-200 nm were dispersed in anhydrous ethanol to prepare a uniform suspension with a solid content of 5 wt%. The suspension was then drop-coated onto a stainless steel substrate with a size of 10 cm × 10 cm and dried in a vacuum drying oven at 60 °C for 12 h. The substrate was then loaded into a PECVD device.

[0033] The plasma power is set to 200-400W, the working pressure to 50-200Pa, and the background vacuum of the deposition chamber to be better than 1Pa.

[0034] Preparation of the SiC transition layer: A mixture of silane (SiH4, purity ≥99.999%) and methane (CH4, purity ≥99.999%) gas is introduced, with a SiH4 flow rate of 10-30 sccm and a CH4 flow rate of 20-50 sccm. The substrate temperature is controlled at 650-750℃. Plasma glow discharge initiates the gas-phase reaction, generating a SiC transition layer in situ on the nano-silicon surface with a thickness controlled at 8-12 nm. The main reaction equations for this stage are: SiH4→Si+2H2 CH4→C+2H2 Si + C → SiC Amorphous carbon layer deposition: Close the SiH4 gas path and keep only the CH4 gas path. Increase the flow rate to 50-80 sccm, lower the substrate temperature to 450-550℃, and continue plasma-enhanced carbon deposition to form an amorphous carbon layer on the outside of the SiC layer with a thickness controlled at 25-35 nm.

[0035] Performance testing: The obtained composite material was mixed with binder (PVDF) and conductive agent (SuperP) at a mass ratio of 80:10:10, and then ground and dispersed in N-methylpyrrolidone (NMP) to form a uniform slurry. The slurry was coated onto a copper foil current collector with a coating thickness of 100 μm and dried in a vacuum drying oven at 80 °C for 12 h to obtain the negative electrode sheet.

[0036] A 2032 coin cell was assembled using lithium metal as the counter electrode, a Celgard 2400 polypropylene membrane as the separator, and 1 mol / L LiPF6 / EC and DEC (volume ratio 1:1) as the electrolyte. Assembly was completed in a glove box under an argon atmosphere with a water and oxygen content of <0.1 ppm. Electrochemical performance tests were then conducted. First-time efficiency test: The LandCT2001A battery testing system was used to conduct the first charge-discharge test at a rate of 0.1C. The expected first coulombic efficiency is over 92%. Cycling performance: Capacity retention >90% after 100 cycles at 1C rate; Rate performance: After 10 cycles each at 0.2C, 0.5C, 1C, 2C, and 3C rates, the expected capacity retention at 3C rate is >80%. AC impedance testing (EIS): A PARSTAT2273 electrochemical workstation was used, with a frequency range of 100mHz-1MHz, AC amplitude of 5mV, and expected interface impedance of <50Ω·cm².

[0037] Example 3 This embodiment verifies the effect of SiC phase content on the electrochemical performance of composite materials by systematically adjusting the ratio of organosilicon precursor to carbon source gas. The thickness and phase content of the SiC transition layer directly determine the interfacial bonding strength and lithium-ion transport kinetics.

[0038] Three control flow ratios were set, and the flow ratios of the organosilicon precursor and carbon source gas during the SiC transition layer formation stage were as follows:

[0039] With a fixed amorphous carbon outer layer thickness of 30-35 nm, three sets of composite anode materials were prepared according to the process flow of Example 1, and their electrochemical performance was compared. The test conditions were the same as in Example 2.

[0040] Test results show that: Group A SiC content 5%-10%: The interfacial bonding force is relatively weak. After 50 cycles, the capacity retention rate is only 75% and the interfacial impedance is 65Ω·cm². Group B, with SiC content of 15%-20%, exhibits the best overall performance, achieving a capacity retention of 92% after 100 cycles, a first-cycle efficiency of 93.5%, an interface impedance of 38 Ω·cm², and a 3C rate capacity retention of 82%. Group C, with a SiC content of 25%-30%, exhibits high interfacial mechanical strength but significantly increases lithium-ion diffusion resistance, resulting in an interfacial impedance of 85 Ω·cm² and a 3C rate capacity retention rate of only 60%.

[0041] The results show that the SiC content of Group B, with 15%-20% SiC, has the best overall performance. It ensures high mechanical strength and stress buffering capacity of the SiC transition layer without excessively sacrificing the active capacity of silicon. When the SiC content is too low, the interfacial bonding force is insufficient and the cycle stability is poor. When the SiC content is too high, the lithium-ion diffusion resistance increases and the high-rate performance decreases.

[0042] The experimental data shows that the increase in SiC content leads to an increase in interface impedance, which is due to the intrinsic characteristics of SiC semiconductors. Therefore, it is necessary to strictly control the mass fraction of SiC phase in the range of 15% to 20% to achieve a balance between stress buffering and charge conduction.

[0043] Example 4 In this embodiment, magnetron sputtering technology is used to deposit a SiC transition layer and an amorphous carbon layer on the surface of nano-silicon particles to verify the applicability of different deposition techniques to the technical solution of the present invention.

[0044] Nano-sized silicon particles with a diameter of 80-120 nm were placed in the vacuum chamber of a magnetron sputtering device, with a chamber background vacuum level better than 5 × 10⁻⁶. -4 Pa, the sputtering gas is high-purity argon (purity ≥99.999%).

[0045] SiC transition layer deposition: Using SiC ceramic target (purity ≥99.9%), sputtering power of 100-150W, working pressure of 0.5-1.0Pa, argon flow rate of 20-30sccm, and deposition time of 5-10min, a SiC transition layer with a thickness of 8-12nm is formed on the surface of nano-silicon particles.

[0046] Amorphous carbon layer deposition: Replace with graphite target (purity ≥99.9%), sputtering power 80-120W, working pressure 0.3-0.8Pa, argon flow rate 15-25sccm, deposition time 15-25min, to form an amorphous carbon layer with a thickness of 30-40nm on the outside of the SiC transition layer.

[0047] The composite material prepared in this embodiment has structural features and electrochemical properties comparable to those in Example 1, verifying the feasibility of magnetron sputtering technology as an alternative deposition method to the technical solution of this invention.

[0048] Example 5 This embodiment verifies the effect of annealing temperature on the microstructure and electrochemical performance of the double-coated carbon-silicon composite anode material.

[0049] Double-coated silicon-carbon composite particles were prepared according to the process flow of Example 1. Three sets of annealing temperatures were set for comparative experiments: 500℃, 600℃, and 700℃. The holding time was 2h, the heating rate was 5℃ / min, and the cooling method was furnace cooling.

[0050] XRD characterization revealed that the SiC phase exhibited the best crystallinity and highest diffraction peak intensity at an annealing temperature of 600℃. At an annealing temperature of 500℃, SiC crystallization was incomplete, and interfacial stress relief was insufficient. An annealing temperature of 700℃ may lead to an increase in the graphitization of the amorphous carbon layer, a decrease in specific surface area, and an impact on lithium-ion transport channels.

[0051] Electrochemical testing results show that when the annealing temperature is 600℃, the initial coulombic efficiency of the composite material reaches 93.2%, and the capacity retention rate after 100 cycles is 91.5%, exhibiting the best overall performance. For industrial-scale preparation, a 600℃, 2-hour holding time process is preferred; if annealing at 700℃ is used, the holding time should be shortened to less than 1 hour to avoid degradation of electrochemical rate performance. The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A carbon-silicon composite anode material, characterized in that, include: Nano-silicon cores, wherein the particle size of the nano-silicon cores is 50-200 nm; A SiC transition layer is formed on the surface of the nano-silicon core, with a thickness of 5-20 nm, and is bonded to the nano-silicon core by atomic-level Si-C chemical bonding. An amorphous carbon outer layer, which covers the outside of the SiC transition layer, has a thickness of 20-50 nm.

2. The carbon-silicon composite anode material according to claim 1, characterized in that: The mass fraction of the SiC phase in the SiC transition layer is 5%-30% based on the total mass of the SiC transition layer.

3. The carbon-silicon composite anode material according to claim 1, characterized in that: The outer layer of the amorphous carbon is an amorphous carbon with a mixed sp² / sp³ structure.

4. The carbon-silicon composite anode material according to claim 1, characterized in that: The particle size of the nano-silicon core is 80-150 nm.

5. The carbon-silicon composite anode material according to claim 1, characterized in that: The thickness of the SiC transition layer is 10-15 nm.

6. A method for preparing the carbon-silicon composite anode material according to any one of claims 1-5, characterized in that, Includes the following steps: (1) The silicon source material is nano-sized to obtain nano-silicon particles with a particle size of 50-200 nm; (2) The nano-silicon particles are placed in a chemical vapor deposition apparatus and heated to 600-800°C. At the same time, an organosilicon precursor and a carbon source gas are introduced to form a SiC transition layer in situ on the surface of the nano-silicon particles. (3) Reduce the temperature to 400-600℃ and continue to introduce carbon source gas for pyrolysis deposition to form an amorphous carbon outer layer on the outside of the SiC transition layer.

7. The method for preparing the carbon-silicon composite anode material according to claim 6, characterized in that: The organosilicon precursor in step (2) is silane, and the carbon source gas is acetylene, methane or a mixture thereof.

8. The method for preparing the carbon-silicon composite anode material according to claim 6, characterized in that: Steps (2) and (3) involve depositing the coating layer using magnetron sputtering or plasma-enhanced chemical vapor deposition.

9. The method for preparing the carbon-silicon composite anode material according to claim 6, characterized in that: In step (2), the thickness of the SiC transition layer is adjusted by controlling the reaction time and the flow ratio of the organosilicon precursor to the carbon source gas.

10. The method for preparing the carbon-silicon composite anode material according to claim 6, characterized in that: Step (3) is followed by an annealing process in an inert atmosphere. The annealing temperature is 550~650℃, and the overall annealing range is controlled between 500-700℃. The 700℃ high temperature can only be held for a short time ≤1h. Long-term annealing at 700℃ will cause excessive graphitization of amorphous carbon and a decrease in the specific surface area of ​​the material. The holding time is 1-3h.